PREPARATION AND BARRIERS IN IMPLEMENTATION INTEROPERABILITY SYSTEMS AMONG HOSPITALS: A SYSTEMATIC REVIEW (Proceedings of the International Conference on Public Health, 2021)
Hospital Information System must provide innovative services in digitals era. Theinteroperability systems made data interconnected between hospitals, health services and the ministryof health. This system is urgently needed to improve National health services. The aim of the study toassess the preparation, barriers and benefit of interoperability system implementation. The study wasa systematic review of journal articles by assessing several databases, from Pubmed, Proquest,EBSCO, and Springer Link to identify relevant studies with PRISMA. The keyword is “HealthInformation Interoperability, Hospital and Implementation”. Ten articles were obtained whichmatched the inclusion and exclusion criteria. These articles explained how the system can be applied,from the preparation of the infrastructure, such as the standard systems that have been adopted, FastHealthcare Interoperability Resources (FHIR) from Health Level 7 (HL7). The barriers were thestandardized data between hospitals with same vendors, so the hospitals were reluctant to implementit. The benefit was the hospital services improve quality in accuracy, legibility, completeness andconsistency of documents. Hoped that interoperability can make health information systems moreeffective by preventing repeated examinations and so that can reduce health costs. This system is a bigchallenge throughout the world, the role of government and policymakers is needed in implementation.
Keywords: Health Information Interoperability, Hospital, Implementation, Systematic Review